Multilayer electronic components

JP2026169141APending Publication Date: 2026-10-16SAMSUNG ELECTRO MECHANICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2026033782
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2025-04-03
Filing Date
2026-03-04
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

【0007】 本開示の様々な効果のうち一つとして、信頼性に優れた積層型電子部品を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026169141000001_ABST
    Figure 2026169141000001_ABST
Patent Text Reader

Abstract

We provide highly reliable stacked electronic components. [Solution] A stacked electronic component according to one embodiment of the present disclosure includes a body comprising a dielectric layer containing Ba, Ti, and Ge, and internal electrodes arranged alternately with the dielectric layer, and external electrodes arranged on the body, wherein the dielectric layer includes a plurality of dielectric crystal grains and grain boundaries arranged between adjacent dielectric crystal grains, and the average content of Ge relative to Ti at the grain boundaries may be 0.2 at% or more and 4.5 at% or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This disclosure relates to a stacked electronic component. [Background technology]

[0002] Multi-Layered Ceramic Capacitors (MLCCs), a type of multilayer electronic component, are chip-type capacitors mounted on printed circuit boards of various electronic products such as liquid crystal displays (LCDs), plasma display panels (PDPs), computers, smartphones, and mobile phones, playing a role in charging or discharging electricity. Due to their advantages of being small, yet guaranteeing high capacitance and being easy to mount, MLCCs are used as components in a wide range of electronic devices.

[0003] To miniaturize MLCCs, the dielectric layer and internal electrodes of the MLCC must be made thinner. However, as the thickness of the dielectric layer and internal electrodes decreases, the electric field strength applied to each dielectric layer and internal electrode becomes relatively stronger, which can lead to problems such as a decrease in the high-temperature reliability and humidity resistance reliability of the MLCC. [Overview of the Initiative] [Problems that the invention aims to solve]

[0004] One of the various purposes of this disclosure is to provide highly reliable stacked electronic components.

[0005] However, the purpose of this disclosure is not limited to what is described above, and this will become clearer in the course of describing specific embodiments of this disclosure. [Means for solving the problem]

[0006] A multilayer electronic component according to an embodiment of the present disclosure includes a main body including dielectric layers containing Ba, Ti and Ge, and internal electrodes alternately arranged with the dielectric layers, and external electrodes disposed on the main body, wherein the dielectric layer includes a plurality of dielectric crystal grains and a grain boundary disposed between adjacent dielectric crystal grains, and an average content of Ge relative to Ti at the grain boundary may be 0.2 at% to 4.5 at% or less. [Effects of the Invention]

[0007] As one of various effects of the present disclosure, a multilayer electronic component having excellent reliability can be provided. [Brief Description of the Drawings]

[0008] [Figure 1] It is a perspective view schematically illustrating a multilayer electronic component according to an embodiment of the present disclosure. [Figure 2] It is a cross-sectional view schematically illustrating a cut cross-section taken along line I-I' of Figure 1. [Figure 3] It is a cross-sectional view schematically illustrating a cut cross-section taken along line II-II' of Figure 1. [Figure 4] It is an exploded perspective view schematically illustrating the main body of Figure 1. [Figure 5] It is an enlarged view schematically illustrating region K of Figure 2. [Figure 6] It is an image obtained by photographing a dielectric layer and internal electrodes with a Scanning Transmission Electron Microscope (STEM). [Figure 7] It is an image obtained by photographing a grain boundary of a dielectric layer with a Scanning Transmission Electron Microscope (STEM). [Modes for Carrying Out the Invention]

[0009] Hereinafter, embodiments of the present disclosure will be described with reference to specific embodiments and the accompanying drawings. However, the embodiments of the present disclosure may be modified into several other forms, and the scope of the present disclosure is not limited to the embodiments described below. In addition, the embodiments of the present disclosure are provided to more fully explain the present disclosure to those of ordinary skill in the art. Accordingly, the shape, size, and the like of elements in the drawings may be scaled up or down (or highlighted or simplified) for clearer description, and elements denoted by the same reference numerals in the drawings are the same elements.

[0010] Note that in the drawings, parts irrelevant to the description are omitted to clearly explain the present disclosure, and the size and thickness of each illustrated configuration are arbitrarily shown for the convenience of description, so the present disclosure is not necessarily limited by the illustrations. In addition, components having the same function within the scope of the same idea will be described using the same reference numerals. Further, throughout the entire specification, the expression that a certain part "comprises" a certain component does not exclude other components, but means that other components may be further included, unless otherwise specifically stated to the contrary.

[0011] In the drawings, the X direction may be defined as the thickness (T) direction, the Y direction as the length (L) direction, and the Z direction as the width (W) direction. In the present disclosure, "thickness" may mean the size in the thickness direction, "length" may mean the size in the length direction, and "width" may mean the size in the width direction.

[0012] Multilayer electronic component FIG. 1 is a perspective view schematically illustrating a multilayer electronic component according to an embodiment of the present disclosure, FIG. 2 is a cross-sectional view schematically illustrating a cross-section cut along line I-I' of FIG. 1, FIG. 3 is a cross-sectional view schematically illustrating a cross-section cut along line II-II' of FIG. 1, FIG. 4 is an exploded perspective view schematically illustrating the main body of FIG. 1, and FIG. 5 is an enlarged view schematically illustrating region K of FIG. 2.

[0013] Hereinafter, with reference to Figures 1 to 5, a multilayer electronic component 100 according to one embodiment of the present disclosure will be described in detail. While a multilayer ceramic capacitor will be described as an example of a multilayer electronic component, the present disclosure is not limited to this and can be applied to a variety of multilayer electronic components, such as inductors, piezoelectric elements, varistors, or thermistors.

[0014] The length of the multilayer electronic component 100 may be greater than the width and thickness of the multilayer electronic component 100, but this disclosure is not limited thereto. For example, the length of the multilayer electronic component 100 may be shorter than the width of the multilayer electronic component 100. The width of the multilayer electronic component 100 may be less than or greater than the thickness of the multilayer electronic component 100, and this may vary depending on the target specifications and characteristics of the multilayer electronic component 100.

[0015] A stacked electronic component 100 according to one embodiment of the present disclosure may include a body 110 and external electrodes 131 and 132 disposed on the body 110.

[0016] There are no particular restrictions on the specific shape of the main body 110, but as shown in the figure, the main body 110 can be hexahedral or a similar shape. Due to the shrinkage of the ceramic powder contained in the main body 110 during the firing process and the polishing process on the corners of the main body 110, the main body 110 may not be a perfectly straight hexahedron, but it can be substantially hexahedral.

[0017] The main body 110 may have a first surface 1 and a second surface 2 facing each other in the thickness direction, a third surface 3 and a fourth surface 4 connected to the first surface 1 and the second surface 2 facing each other in the length direction, a fifth surface 5 and a sixth surface 6 connected to the first surface 1, the second surface 2, the third surface 3 and the fourth surface 4 facing each other in the width direction.

[0018] The main body 110 may include dielectric layers 111 and internal electrodes 121 and 122 arranged alternately with the dielectric layers 111. The multiple dielectric layers 111 forming the main body 110 are in a fired state, and the boundaries between adjacent dielectric layers 111 can be integrated to such an extent that they are difficult to confirm without using a scanning electron microscope (SEM).

[0019] The main body 110 may include a capacitance forming section Ac which includes a first internal electrode 121 and a second internal electrode 122 that are alternately arranged with respect to a dielectric layer 111 in between, thereby forming a capacitance. The stacking direction of the internal electrodes 121 and 122 can be in the thickness direction or the width direction. In this disclosure, an embodiment in which the stacking direction of the internal electrodes 121 and 122 is in the thickness direction will be described as a reference.

[0020] The first internal electrode 121 is separated from the fourth surface 4 and can be connected to the first external electrode 131 at the third surface 3. The second internal electrode 122 is separated from the third surface 3 and can be connected to the second external electrode 132 at the fourth surface 4.

[0021] The main body 110 may include cover portions 112 and 113 arranged on both sides facing each other in the thickness direction of the capacitance forming portion Ac, and margin portions 114 and 115 arranged on both sides facing each other in the width direction of the capacitance forming portion Ac. The cover portions 112 and 113 and the margin portions 114 and 115 may have a configuration similar to that of the dielectric layer 111, except that they do not include internal electrodes.

[0022] The external electrodes 131 and 132 may include a first external electrode 131 positioned on the third surface 3 and extending over parts of the first surface 1, the second surface 2, the fifth surface 5, and the sixth surface 6, and a second external electrode 132 positioned on the fourth surface 4 and extending over parts of the first surface 1, the second surface 2, the fifth surface 5, and the sixth surface 6.

[0023] The type and form of the external electrodes 131 and 132 are not particularly limited, and they may have a multilayer structure. For example, the external electrodes 131 and 132 may include a base electrode layer that contacts the internal electrodes 121 and 122 and a plating layer disposed on the base electrode layer.

[0024] The above-mentioned base electrode layer may be a fired electrode layer containing metal and glass. The metal contained in the fired electrode layer may include, for example, Cu, Ni, Pd, Pt, Au, Ag, Pb and / or alloys containing these. The glass contained in the fired electrode layer may include, for example, one or more oxides of Ba, Ca, Zn, Al, B and Si.

[0025] The above-mentioned base electrode layer may consist only of a fired electrode layer, but the disclosure is not limited thereto, and the base electrode layer may include a fired electrode layer containing metal and glass, and a resin electrode layer disposed on the fired electrode layer and containing metal particles and resin.

[0026] The metal particles contained in the resin electrode layer may include one or more spherical particles and flake-shaped particles. The metal particles contained in the resin electrode layer may include, for example, Cu, Ni, Pd, Pt, Au, Ag, Pb, Sn and / or alloys containing these. The resin contained in the resin electrode layer may include, for example, one or more epoxy resin, acrylic resin, and ethylcellulose.

[0027] The above-mentioned plating layer may include, for example, Ni, Sn, Pd, and / or alloys containing these, and may be formed in multiple layers. The above-mentioned plating layer may be, for example, a Ni plating layer or a Sn plating layer, or a Ni plating layer and a Sn plating layer may be formed sequentially. The above-mentioned plating layer may include multiple Ni plating layers and / or multiple Sn plating layers.

[0028] In the drawings, a structure in which the multilayer electronic component 100 has two external electrodes 131 and 132 is described, but the present disclosure is not limited thereto, and the number, shape, etc. of the external electrodes 131 and 132 may vary according to the form of the internal electrodes 121 and 122 and other purposes.

[0029] The dielectric layer 111 may contain Ba and Ti. The dielectric layer 111 may contain, for example, a perovskite-type compound represented by ABO₃ as a main component. The A may contain Ba, and the B may contain Ti. The perovskite-type compound may be, for example, BaTiO₃, (Ba 1-x Ca x )TiO₃(0<x<1), Ba(Ti 1-y Ca y )O₃(0<y<1), (Ba 1-x Ca x )(Ti 1-y Zr y )O₃(0<x<1, 0<y<1) and Ba(Ti 1-y Zr y )O₃(0<y<1). In the present disclosure, the main component may mean a component that occupies a relatively larger proportion than other components, and may mean a component that is 50 wt% or more, or 50 at% or more based on the content of the entire composition or the entire dielectric layer.

[0030] The dielectric layer 111 may include a plurality of dielectric crystal grains 111a and grain boundaries 111b disposed between adjacent dielectric crystal grains. That is, the grain boundary 111b may mean a boundary between adjacent dielectric crystal grains, and the dielectric crystal grain 111a may have a form surrounded by a plurality of grain boundaries 111b. The boundary between the dielectric crystal grain 111a and the grain boundary 111b can be defined by dividing a portion with a difference in brightness and darkness by a method such as binarizing an image captured by a transmission electron microscope.

[0031] As the thickness of the dielectric layer 111 and the internal electrodes 121 and 122 of the multilayer electronic component 100 decreases, the electric field strength applied to each layer of dielectric layer 111 and internal electrodes 121 and 122 becomes relatively stronger, which may reduce the reliability of the multilayer electronic component 100. On the other hand, the main component constituting the insulation resistance (IR), which indicates the reliability of a dielectric, is known to be grain boundary resistance due to Schottky-type energy barriers present at the grain boundaries.

[0032] The dielectric layer 111 may contain Ge. When Ge is distributed at the grain boundaries 111b, it acts as an energy barrier that increases grain boundary resistance, thereby improving the reliability of the multilayer electronic component 100. However, if Ge is excessively distributed at the grain boundaries 111b, it can cause localized electric field concentration while abnormally increasing grain boundary resistance, or excessively suppress grain growth of the dielectric crystal grains 111a, thereby actually reducing the reliability of the multilayer electronic component 100. Therefore, in order to improve the reliability of the multilayer electronic component 100, it is necessary to appropriately adjust the Ge content present at the grain boundaries 111b.

[0033] According to one embodiment of the present disclosure, the average content of Ge relative to Ti at the grain boundary 111b (C GB ) may be between 0.2 at% and 4.5 at%. GB When the above numerical range is satisfied, the reliability of the stacked electronic component 100 can be effectively improved.

[0034] The average Ge content relative to Ti at grain boundary 111b (C GBAn example of a method for measuring the content of a grain boundary is as follows: First, the length-thickness cross section (hereinafter referred to as the measurement cross section) of the multilayer electronic component 100 is exposed by polishing up to the center in the width direction. After this, a thin film sample for scanning transmission electron microscopy (STEM) observation is prepared through FIB microsampling, and the surface damage layer is removed from the thin film sample by Ar ion milling. After this, the electron beam probe diameter is set to approximately 0.2 nm, and analysis is performed at one point of the grain boundary. At this time, analysis is performed only on the grain boundary 111b perpendicular to the electron beam. The components of the grain boundary 111b can be analyzed using energy-dispersive X-ray analysis equipment (EDS) mounted on the scanning transmission electron microscope (STEM). The Ge content relative to Ti at the grain boundary 111b can be measured from the value obtained by dividing the measured Ge content (at%) by the Ti content (at%). Furthermore, after performing the above content measurement at 10 or more grain boundaries 111b, the average content of Ge relative to Ti at the grain boundary 111b (C GB It can measure ).

[0035] In one embodiment, the average content (at%) of Ge relative to Ti within a plurality of dielectric crystal grains 111a may be smaller than the average content (at%) of Ge relative to Ti at the grain boundaries 111b. Ge is not dissolved in the dielectric crystal grains 111a but is distributed at the grain boundaries 111b, improving the insulation resistance of the dielectric layer 111. The content of Ge relative to Ti within a plurality of dielectric crystal grains 111a can be measured from the value obtained by dividing the Ge content (at%) measured via EDS by the Ti content (at%). Furthermore, after performing the above content measurement on 10 or more dielectric crystal grains 111a, the average content of Ge relative to Ti within a plurality of dielectric crystal grains 111a can be obtained by averaging the measured values. DG It can measure ).

[0036] In one embodiment, the internal electrodes 121 and 122 may include a Ni-Ge alloy. By firing Ni and Ge together in a reducing atmosphere, a uniform Ni-Ge alloy can be formed on the internal electrodes 121 and 122. The Ni-Ge alloy reduces the grain boundary energy and surface tension of Ni, improving the smoothness and connectivity of the internal electrodes 121 and 122. Improved smoothness of the internal electrodes 121 and 122 allows for effective dispersion of the electric field strength applied to the dielectric layer 111, even if the thickness of the dielectric layer 111 is reduced.

[0037] Furthermore, alloying the quasimetallic Ge with Ni improves the insulation of the interface between the dielectric layer 111 and the internal electrodes 121 and 122, thereby improving the reliability of the multilayer electronic component 100. In addition, since the sintering rate of Ni is slowed during the alloying process with Ge, the electrode connectivity is further improved, enabling the realization of a multilayer electronic component 100 with higher capacitance.

[0038] In one embodiment, the average content of Ge relative to Ni in the internal electrodes 121 and 122 (C IE ) may be between 0.32 at% and 6.3 at%. When the above numerical range is satisfied, the capacitance and reliability of the multilayer electronic component 100 can be improved more effectively. In addition, Ge contained in the internal electrodes 121 and 122 can diffuse into the grain boundaries 111b of the dielectric layer 111 during the firing process. Therefore, the above C IE When the above numerical range is satisfied, the above C GB This allows for more effective control.

[0039] On the other hand, the internal electrodes 121 and 122 may further include one or more conductive metals from among Cu, Ag, Pd, Au, Al, and Sn, in addition to the Ni-Ge alloy, but the disclosure is not limited thereto.

[0040] The Ge content (at%) relative to Ni in the internal electrodes can be determined by dividing the Ge content (at%) measured using STEM-EDS at one point inside the internal electrodes 121 and 122 by the Ni content (at%). Alternatively, the above content measurement can be performed at any three or more points on one internal electrode 121 or 122, and / or at three or more internal electrodes 121 or 122, and then averaging the measured values ​​to obtain the average Ge content (C) relative to Ni in the internal electrodes. IE It can measure ).

[0041] The following section specifically describes the minor components that may be included in the dielectric layer 111. The minor components described below are explained based on the number of moles of the elements, and can be calculated by converting this to the content of oxides or carbonates added as additives before firing. The content of the above minor component elements can be measured by various methods such as SEM-EDS, TEM-EDS, and STEM-EDS.

[0042] a) First subcomponent The dielectric layer 111 may further contain a first subcomponent comprising one or more of Y, Dy, Tb, Ho, Er, Gd, Ce, Nd, Sm, Tm, La, and Yb. The first subcomponent can improve the high-temperature accelerated lifetime of the multilayer electronic component 100.

[0043] The content of the above-mentioned first minor component may be between 2.5 moles and 8.0 moles per 100 moles of Ti. If the content of the above-mentioned first minor component is less than 2.5 moles or more than 8.0 moles, the dielectric constant at room temperature or the insulation resistance characteristics may decrease.

[0044] The dielectric layer 111 may contain, for example, Dy. In one embodiment, the average content of Dy relative to Ti at the grain boundary 111b may be between 2.0 at% and 5.0 at%. When the above numerical range is satisfied, the reliability of the multilayer electronic component 100 can be improved more effectively.

[0045] b) Second subcomponent The dielectric layer 111 may further contain a second subcomponent comprising one or more of Mn, V, Cr, Fe, Co, Ni, Cu, Co, and Zn. The second subcomponent can play a role in reducing the firing temperature, dielectric properties, and high-temperature accelerated lifetime characteristics of the multilayer electronic component 100.

[0046] The content of the above-mentioned second minor component may be between 0.2 moles and 1.4 moles per 100 moles of Ti. If the content of the above-mentioned second minor component is less than 0.2 moles per 100 moles of Ti, the high-temperature accelerated lifetime may deteriorate, and if it exceeds 1.4 moles per 100 moles of Ti, the dielectric constant may deteriorate.

[0047] c) Third subcomponent The dielectric layer 111 may further contain a third subcomponent containing Mg. This third subcomponent can provide reduction resistance and increase the RC value.

[0048] The content of the above-mentioned third minor component may be between 0 moles and 2.0 moles or less per 100 moles of Ti. If the content of the above-mentioned third minor component exceeds 2.0 moles, the TCC may not satisfy the X7R characteristics.

[0049] In one embodiment, the average Mg content relative to Ti at the grain boundary 111b may be between 0.2 at% and 1.0 at%. When the above numerical range is satisfied, the reliability of the multilayer electronic component 100 can be improved more effectively.

[0050] d) Fourth subcomponent The dielectric layer 111 may further contain a fourth subcomponent comprising one or more of Si and Al. Si and / or Al, like Ge, act as energy barriers that increase grain boundary resistance when distributed at the grain boundaries 111b, thereby improving the reliability of the multilayer electronic component 100.

[0051] In particular, Si and / or Al have high chemical stability and can be distributed relatively uniformly at the grain boundaries 111b, and can also play a role in maintaining the uniform size of the dielectric grains 111a.

[0052] Therefore, the average content (at%) of Si relative to Ti at the grain boundary 111b may be greater than the average content (at%) of Ge relative to Ti at the grain boundary 111b, but this disclosure is not limited thereto.

[0053] Similarly, the average content (at%) of Al relative to Ti at the grain boundary 111b may be greater than the average content (at%) of Ge relative to Ti at the grain boundary 111b, but this disclosure is not limited thereto.

[0054] The average Si content relative to Ti at the grain boundary 111b may be, for example, 7.0 at% or more and 9.0 at% or less, but this disclosure is not limited thereto. The average Al content (at%) relative to Ti at the grain boundary 111b may be, for example, 8.0 at% or more and 10.0 at% or less, but this disclosure is not limited thereto.

[0055] The average content of Dy relative to Ti, the average content of Mg relative to Ti, the average content of Si relative to Ti, and the average content of Al relative to Ti at grain boundary 111b are measured by STEM-EDS using Dy content (at%), Mg content (at%), Si content (at%), and Al content (at%), respectively, instead of Ge content (at%), as described above. GB It can be measured using a similar method.

[0056] The average size of the dielectric crystal grains 111a is not particularly limited, but may be between 120 nm and 200 nm. The average size of the dielectric crystal grains 111a can be measured, for example, by taking an image of the measurement cross-section using a scanning electron microscope (SEM).

[0057] The average thickness td of the dielectric layer 111 is not particularly limited. The average thickness td of the dielectric layer 111 may be, for example, 0.05 μm or more and 2.5 μm or less, 0.05 μm or more and 1.0 μm or less, 0.05 μm or more and 0.5 μm or less, or 0.05 μm or more and 0.4 μm or less.

[0058] The average thickness te of the internal electrodes 121 and 122 is not particularly limited. The average thickness te of the internal electrodes 121 and 122 may be, for example, 0.05 μm or more and 1.0 μm or less, 0.05 μm or more and 0.5 μm or less, or 0.05 μm or more and 0.4 μm or less.

[0059] The average thickness td of the dielectric layer 111 and the average thickness te of the internal electrodes 121 and 122 can be measured by scanning the measurement cross-section with a scanning electron microscope (SEM) at 10,000x magnification. More specifically, the average thickness td of the dielectric layer 111 can be measured by measuring its thickness at multiple points on one dielectric layer 111, for example, five points equally spaced in the longitudinal direction, and then calculating the average value. Similarly, the average thickness te of the internal electrodes 121 and 122 can be measured by measuring its thickness at multiple points on one internal electrode 121 or 122, for example, five points equally spaced in the longitudinal direction, and then calculating the average value. The five equally spaced points can be specified in the capacitance forming section Ac. On the other hand, if such average value measurements are performed for 10 dielectric layers 111 and 10 internal electrodes 121 and 122, and then the average value is measured, the average thickness td of the dielectric layer 111 and the average thickness te of the internal electrodes 121 and 122 can be further generalized.

[0060] The average thickness tc of the cover portions 112 and 113 is not particularly limited. The average thickness of the cover portions 112 and 113 may be, for example, 5 μm to 100 μm, 5 μm to 50 μm, 5 μm to 30 μm, or 5 μm to 20 μm. Here, the average thickness tc of the cover portions 112 and 113 refers to the average thickness of the first cover portion 112 and the second cover portion 113, respectively. The average thickness tc of the cover portions 112 and 113 may also be the average value of the thickness measured at five equally spaced points in the longitudinal direction in the measurement cross-section.

[0061] Hereinafter, an example of a method for forming a multilayer electronic component 100 will be described. However, the manufacturing method of the multilayer electronic component 100 is not limited thereto.

[0062] First, ceramic powder for forming the dielectric layer 111 is prepared. The ceramic powder may be a perovskite-type compound powder represented by ABO₃. The ceramic powder is, for example, BaTiO₃, (Ba 1-x Ca x )TiO₃ (0<x<1), Ba(Ti 1-y Ca y )O₃ (0<y<1), (Ba 1-x Ca x )(Ti 1-y Zr y )O₃ (0<x<1, 0<y<1), and Ba(Ti 1-y Zr y )O₃ (0<y<1). The BaTiO₃ powder can be synthesized, for example, by reacting a titanium raw material such as titanium dioxide with a barium raw material such as barium carbonate. Examples of the synthesis method for the ceramic powder include a solid phase method, a sol-gel method, a hydrothermal synthesis method, and the like, but the present disclosure is not limited thereto. Next, after drying and pulverizing the prepared ceramic powder, an organic solvent such as ethanol, a binder such as polyvinyl butyral, first to fourth subcomponent powders, and the like are mixed to produce a ceramic slurry, and the ceramic slurry is applied onto a carrier film and dried to prepare a ceramic green sheet.

[0063] Next, an internal electrode pattern can be formed by printing a conductive paste for internal electrodes containing metal powder, a binder, an organic solvent and the like at a predetermined thickness on the ceramic green sheet using a screen printing method, a gravure printing method or the like. The metal powder may include, for example, Ni powder. Furthermore, the metal powder may further include one or more of Cu, Ag, Pd, Au, Al, and Sn powders.

[0064] The conductive paste for the internal electrode described above may contain GeO2 powder. The content of GeO2 powder in the conductive paste for the internal electrode is not particularly limited, but may be 0.5 wt% to 10 wt% relative to Ni.

[0065] After this, the ceramic green sheet with the printed internal electrode pattern is peeled off the carrier film, and then a predetermined number of layers of ceramic green sheets with the printed internal electrode pattern are laminated and pressed together to form a ceramic laminate. A predetermined number of ceramic green sheets without the internal electrode pattern may be laminated on the upper and lower parts of the ceramic laminate to form cover portions 112 and 113 after firing. After this, the ceramic laminate can be cut to have a predetermined chip size, and the cut chips can be fired to form a main body 110 including a dielectric layer 111 and internal electrodes 121 and 122. The firing can be carried out, for example, in a 1.0%H2 / 99.0%N2~3.5%H2 / 96.5%N2 (H2O / H2 / N2 atmosphere) at a temperature of 1000°C to 1400°C for 1 to 3 hours.

[0066] During the firing process described above, Ni and Ge are alloyed, and the internal electrodes 121 and 122 can contain a Ni-Ge alloy. Furthermore, Ge contained in the conductive paste for the internal electrodes can diffuse into the dielectric layer 111 during the firing process, and the diffused Ge can be distributed at the grain boundaries 111b, thereby adjusting the average Ge content relative to Ti at the grain boundaries. However, this disclosure is not limited thereto, and the average Ge content relative to Ti at the grain boundaries can also be adjusted by separately adding GeO2 powder to the ceramic slurry for forming the dielectric layer 111.

[0067] Next, external electrodes 131 and 132 are formed. For example, if the base electrode layer includes a fired electrode layer, the main body 110 can be dipped in a conductive paste for external electrodes containing metal powder, glass frit, binder, and organic solvent, and then the conductive paste for external electrodes can be fired at a temperature of 500°C to 900°C to form a fired electrode layer.

[0068] For example, if the base electrode layer includes a resin electrode layer, the main body can be dipped in a conductive resin composition containing metal powder, resin, binder, and organic solvent, and then cured at a temperature of 250°C to 550°C to form the resin electrode layer.

[0069] Furthermore, an electrolytic plating method and / or an electroless plating method may be further used to form a plating layer on the above-mentioned base electrode layer.

[0070] (Examples) The present disclosure will be described in more detail below through examples. However, the following examples are provided to aid in a concrete understanding of the present disclosure and do not limit the scope of the present disclosure.

[0071] Sample chips of size 0603 (length: approximately 0.6 mm, width: approximately 0.3 mm, thickness: approximately 0.3 mm) were manufactured using the method described above. Sample chips for the examples and comparative examples were prepared while adjusting the GeO2 content relative to Ni in the conductive paste for the internal electrodes from 0 wt% to 12 wt%.

[0072] Afterward, the length-thickness cross-sections were exposed by polishing each sample chip to the center in the width direction, and thin film samples for scanning transmission electron microscopy (STEM) observation were fabricated via FIB microsampling. Next, the surface damage layer of the thin film samples was removed using Ar ion milling, and then STEM-EDS analysis was performed under conditions of an acceleration voltage of 200 kV and a probe diameter of 0.2 nm. Figure 6 is an image of the dielectric layer and internal electrodes taken with a scanning transmission electron microscope (STEM). Figure 7 is an image of the grain boundary 111b of the dielectric layer taken with a scanning transmission electron microscope (STEM).

[0073] Subsequently, the Ge content (at%) relative to Ti was measured at 10 grain boundaries perpendicular to the electron beam. Furthermore, the average value after performing the above content measurements on 20 sample chips for each of the comparative example and example was measured to determine the average Ge content (C) relative to Ti at the grain boundaries. GB ) was derived.

[0074] Similarly, by measuring the Ge content relative to Ti at any three points inside the internal electrode using STEM-EDS, and then measuring the average value after performing the above content measurements on 20 sample chips for each comparative example and example, the average Ge content relative to Ni in the internal electrode (C) can be determined. IE ) was derived.

[0075] Subsequently, high-temperature accelerated lifetime evaluation was performed on 40 samples each of the comparative examples and the examples under conditions of 125°C and 9.5V, and the mean time to failure (MTTF) value was measured. At this time, the time when the insulation resistance became 10kΩ or less was defined as the failure time, and the MTTF value of Comparative Example 1 was set as the baseline value 1, and the relative values ​​of the other examples and comparative examples are listed.

[0076] [Table 1]

[0077] Referring to Table 1 above, C GB In the case of Comparative Examples 1 and 2, where the MTTF of the sample chip is less than 0.2 at%, the above C GB It can be confirmed that the MTTF improves sharply when the value is 0.2 at% or higher. However, in the case of Comparative Example 3, the above C GB When the concentration exceeds 4.5 at%, it is confirmed that an excess of Ge is contained within the grain boundaries, which actually lowers the MTTF.

[0078] As a result, as in Examples 1 to 5, the average content of Ge relative to Ti at the grain boundary (C GB When the ratio is between 0.2 at% and 4.5 at%, it can be confirmed that the reliability of the multilayer electronic component is sufficiently improved.

[0079] This disclosure is not limited by the embodiments described above and the accompanying drawings, but is limited by the claims attached. Therefore, within the scope of the technical idea of ​​this disclosure as described in the claims, various forms of substitution, modification, and alteration are possible by a person with ordinary skill in the art, and these also fall within the scope of this disclosure.

[0080] Furthermore, the expression "one embodiment" does not mean that each embodiment is identical to the others, but is provided to highlight and explain the unique and distinct characteristics of each embodiment. However, the above-presented embodiments do not preclude their realization in combination with the characteristics of other embodiments. For example, even if a matter described in one embodiment is not described in another embodiment, it can be understood as a description related to the other embodiment, as long as there is no contradictory or contrary explanation of that matter in the other embodiment.

[0081] In this disclosure, the term "connected" includes not only direct connection but also indirect connection via an adhesive layer or the like. Furthermore, the term "electrically connected" includes both physically connected and non-connected cases. In addition, expressions such as "first," "second," etc., are used to distinguish one component from another and do not limit the order and / or importance of the components. In some cases, without departing from the scope of the rights, the first component may be named the second component, and similarly, the second component may be named the first component. [Explanation of Symbols]

[0082] 100 Stacked Electronic Components 110 Main Unit 111 Dielectric layer 111a Dielectric crystal grains 111b Grain boundary 112, 113 Cover section 114, 115 Margin section Internal electrodes 121 and 122 131, 132 External electrodes

Claims

1. A body comprising a dielectric layer containing Ba, Ti, and Ge, and internal electrodes arranged alternately with the dielectric layer, The body includes an external electrode disposed on the main body, The dielectric layer includes a plurality of dielectric crystal grains and grain boundaries arranged between adjacent dielectric crystal grains. A multilayer electronic component in which the average content of Ge relative to Ti at the grain boundaries is 0.2 at% or more and 4.5 at% or less.

2. The stacked electronic component according to claim 1, wherein the internal electrode comprises a Ni-Ge alloy.

3. The multilayer electronic component according to claim 2, wherein the average content of Ge relative to Ni in the internal electrode is 0.32 at% or more and 6.3 at% or less.

4. The stacked electronic component according to claim 1, wherein the average content (at%) of Ge relative to Ti within the plurality of dielectric crystal grains is smaller than the average content (at%) of Ge relative to Ti at the grain boundaries.

5. The dielectric layer is ABO 3 It contains a perovskite-type compound represented by as its main component, The stacked electronic component according to claim 1, wherein A includes Ba and B includes Ti.

6. The laminated electronic component according to claim 1, wherein the dielectric layer further comprises one or more of Y, Dy, Tb, Ho, Er, Gd, Ce, Nd, Sm, Tm, La, and Yb.

7. The laminated electronic component according to claim 1, wherein the dielectric layer further comprises one or more of Mn, V, Cr, Fe, Ni, Cu, Co, and Zn.

8. The stacked electronic component according to claim 1, wherein the dielectric layer further comprises Mg.

9. The multilayer electronic component according to claim 1, wherein the dielectric layer further comprises one or more of Si and Al.

10. The stacked electronic component according to claim 1, wherein the average content (at%) of Si relative to Ti at the grain boundary is greater than the average content (at%) of Ge relative to Ti at the grain boundary.

11. The stacked electronic component according to claim 1, wherein the average content (at%) of Al relative to Ti at the grain boundary is greater than the average content (at%) of Ge relative to Ti at the grain boundary.

12. The stacked electronic component according to claim 1, wherein the average content of Dy relative to Ti at the grain boundaries is 2.0 at% or more and 5.0 at% or less.

13. The stacked electronic component according to claim 1, wherein the average content of Mg relative to Ti at the grain boundaries is 0.2 at% or more and 1.0 at% or less.

14. The stacked electronic component according to claim 1, wherein the average size of the plurality of dielectric crystal grains is 120 nm or more and 200 nm or less.